Climate Change 2022 Mitigation of Climate Change: Urban System - LIMMEECHOKCHAI, Bundit; Kongphunphin, Chompoonut; Winyuchakrit, Pornphimol; Pita, Piti; Misila, Pemika (International Journal of Building, Urban, Interior and Landscape Technology, 2024)
The Sixth Assessment Report of the Intergovernmental Panel on Climate Change (IPCC-AR6) assesses literature on the scientific, technological, environmental, economic, and social aspects of mitigation of climate change. The IPCC-AR6 integrates factors of developments in the UN Framework Convention on Climate Change (UNFCCC) process. It includes the Kyoto Protocol and the Paris Agreement, and the UN 2030 Agenda for Sustainable Development including the Sustainable Development Goals (SDGs). This paper reviews the urban system and its pathways in transition to the net zero emissions. The key messages of urban mitigation in the IPCC-AR6 are presented. It is found that the urban green and blue infrastructure can contribute to climate resilience through carbon sequestration, emissions reduction, and energy and material efficiency. It also contributes multiple co-benefits. To achieve urban transformational changes, it requires climate finance and engagement of multiple scales of governance. This includes governments and non-state actors. A knowledge gap to achieve net-zero-emissions cities is highlighted, and a case study of climate resilient development in Thailand’s building sectors towards a low carbon society is discussed.